How participation in deliberative engagement affects awareness of, and attitudes towards, genomics research and data sharing: evidence from rural Ghana - Irene Honam Tsey; Pamela Emefa Selormey; John Ganle; Patricia Akweongo; Paulina Tindana (BMC Medical Ethics)
Abstract Background Deliberative engagement offers an opportunity for communities to provide informed opinions on complex ethical, legal, and social issues in genomic research and biobanking. However, its use is limited, particularly in resource-constrained settings like Ghana. This study examines the influence of deliberative engagement on participants’ awareness of genomic research and attitudes towards data sharing. Methods This research forms part of a larger mixed-methods study exploring deliberative methods for community engagement in genomics research in Ghana. Using a quasi-experimental one-group pretest-posttest design, 66 participants completed a baseline survey assessing awareness of genomic research and attitudes toward data sharing. Following this, a deliberative workshop was conducted with facilitated discussions. Post-engagement surveys measured changes in awareness and attitudes, and Fisher’s exact test was used to assess statistical significance. Results Respondents (aged 47–67 years; mean 57, SD 4.2) were predominantly male (65%), with 18% having no formal education. Significant improvements were observed in participants’ awareness of genomic research (51–90%, p = 0.001) and confidence in consent processes ensuring privacy and confidentiality. Other variables, including willingness to share samples and trust in data governance, showed no significant change. Conclusions This study demonstrates that deliberative engagement could enhance awareness of genomic research and offers a promising approach to informing, educating, and fostering dialogue on complex ethical issues in genomic research and biobanking, particularly in resource-limited settings. Clinical trial number Not applicable.